Reconsidering migration and class - Van Hear, N (SAGE Publications, 2014)
While once a mainstay of social science, class has lately been eclipsed in much of migration studies by consideration of other forms of social difference, affinity, and allegiance such as ethnicity, gender, generation, and lately religion. This article puts the case for renewing attention on the part class plays in shaping migration – particularly who is able to move and to where. It argues that the form of migration and ultimately its outcomes are shaped by the resources that would-be migrants can muster and that in turn the capacity to mobilize such resources is largely determined by socio-economic background or class. Drawing on Bourdieu, class can be conceived in terms of the disposal of different forms of capital – economic, social, and cultural. Having access to combinations of such capital shapes the routes and channels migrants can follow, the destinations they can reach, and their life chances after migration. The article first reflects briefly on ideas of class in social science and sketches treatment of mobility in the migration literature, before considering the ways in which class, mobility, and immobility shape each other. The article concludes by considering the interplay between migration, class, and collective action among those who move and those who stay, against the background of broader currents of social change and transformation